CHRONIC COLITIS IN MICE INDUCES KIDNEY INJURY: TRANSLATIONAL IMPLICATIONS FOR IBD. (22nd January 2022) - Ducasa, Gloria; Hazime, Hajar; Fernandez, Irina; Brito, Nivis; Santander, Ana; Burgueno, Juan; Abreu, Maria
Abstract: Approximately 4-23% of patients with IBD develop renal complications such as nephrolithiasis, glomerulonephritis, and tubulointerstitial nephritis, which may lead to chronic kidney disease (CKD). Furthermore, it has been shown that younger age of IBD diagnosis increases risk for CKD development and this association is not linked to use of common therapeutic agents for the treatment of IBD, suggesting a disease mediated association of IBD to CKD. IBD is characterized by increased intestinal epithelial permeability. Interestingly, recent literature suggests that gut microbiome regulation plays a role in the development of CKD progression. However, the mechanisms contributing to IBD-mediated CKD have yet to be elucidated. We aimed to establish a model of colitis-mediated kidney injury and to elucidate the role of the microbiome on IBD-mediated CKD development. Two distinct mouse models were used. BL/6 mice were treated with 2% dextran sodium sulfate for 6 days and euthanized, emulating an acute colitis model (A-DSS). We also utilized a chronic colitis model where BL/6 mice underwent three, five-day cycles of 2% dextran sodium sulfate (C-DSS) with a five-day recovery in between each cycle. Spot urines were collected on a weekly basis for albuminuria analysis. Kidneys and intestines were harvested at time of euthanasia. RNA was extracted for gene expression analysis and tissue samples were collected for histological assessment with oil-red-o (ORO) for lipid droplet analysis. A-DSS mice did not experience any difference in kidney inflammatory markers, although intestinal inflammation was increased, as compared to control mice. A-DSS mice also did not demonstrate any difference in bacterial translocation to the kidney. Conversely, C-DSS mice (n=7) experienced an increase in inflammatory genes ( IL1B and TNF ) both in RNA extracted from colon and kidney sections as compared to control mice (n=4). C-DSS mice (n=3) demonstrated increased bacterial translocation (p=0.0003) to the kidney which was associated with increased albumin to creatinine ratios (p=0.0076) as compared to control mice (n=3). ORO staining of whole kidney sections demonstrated that C-DSS mice have increased lipid content as compared to control mice. These data demonstrate that chronic colitis leads to changes in kidney inflammation and physiology seen in renal insufficiency including albuminuria. Furthermore, intestinal inflammation causes increased intestinal epithelial permeability and elevated bacterial translocation to the kidney, which has not been previously described. These data suggest that IBD may increase inflammation in a remote organ possibly through bacterial translocation. Additional studies are underway to identify if this colitis-mediated kidney injury is due to overall bacterial burden or specific bacterial content.